Design and control of a 7-degree-of-freedom symmetric manipulator module for in-orbit operations - Cotrina de los Mozos, Irene; Tang, Gilbert (Institute of Electrical and Electronics Engineers (IEEE), 2024)
This paper proposes a modular redesign of multi-armed robotic systems with application to in-orbit operations. The manipulators that the robot includes are made independent and the connection to the central body is achieved through additional standard interfaces (SI). This grants the system the ability to self-repair through self-reconfiguration. The arms are also upgraded, giving rise to symmetrical manipulators of 7 degrees of freedom (DOF) capable of locomoting by themselves. The models of the new manipulator design are presented along with its nominal workspace. In addition to this, a novel algorithm for the control of the arm is developed based on the F ABRIK approach. This programme is tested using diverse target poses as input and the consequent results are shown too. All the models and sketches were created in SolidWorks; the algorithm was coded in MATLAB.
Keywords: modular design; self-reconfiguration; F ABRIK; inverse kinematics; control algorithm; SolidWorks; MATLAB